2012
DOI: 10.4172/2155-6148.1000254
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the Surgery and Age are Risk Factors for QTc Interval Prolongation under General Anaesthesia with Volatile Anesthetics

Abstract: Individuals who met the inclusion criteria for our study were first screened by the telemetry (MUSE Cardiology Information System, with version 5E, windows Server 2003, from GE Healthcare) in the post anesthetic care unit (PACU) for a prolonged QT interval. We obtained a postoperative 12-lead ECG to confirm either normal or abnormal QTc. Standard 12-lead ECGs were recorded in all subjects at a speed of 25 mm/s with a 10 mm/mV gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We intend to find other anaesthetic agents that could attenuate these QTc interval prolongation because as per the Food and Drug Administration guidelines, QTc interval remains a standard marker to assess the arrhythmic potential of a new drug 29 . Fourth, many of our patients had hypertension or diabetes mellitus, which can influence QTc interval under general anaesthesia 30 . However, the proportions of hypertension or diabetes mellitus were similar among the three groups, and may not have interfered with our findings.…”
Section: Discussionmentioning
confidence: 71%
“…We intend to find other anaesthetic agents that could attenuate these QTc interval prolongation because as per the Food and Drug Administration guidelines, QTc interval remains a standard marker to assess the arrhythmic potential of a new drug 29 . Fourth, many of our patients had hypertension or diabetes mellitus, which can influence QTc interval under general anaesthesia 30 . However, the proportions of hypertension or diabetes mellitus were similar among the three groups, and may not have interfered with our findings.…”
Section: Discussionmentioning
confidence: 71%
“…The same study revealed that 39% of patients exposed to sevoflurane had significant QTc prolongation (>30 ms). Data from another observational study revealed that the presence of diabetes may be a predominant risk factor for perioperative prolongation of QTc interval regardless of the anaesthetic technique 41 . It has to be noted however, that both these studies failed to analyse the torsadogenic parameters such as Tp-e and Tp-e/QTc ratio 40,41 .…”
Section: Discussionmentioning
confidence: 98%